Distribution and accumulation of organochlorine contaminants in sediments and biota from iSmangaliso wetland park (Northern KwaZulu-Natal, South Africa): ecological risks and implications for conservation - Buah-Kwofie, Archibold (My University, 2017)
iSimangaliso Wetland Park World Heritage site, located in northern KwaZulu-Natal, is one of the most biodiverse conservation regions in southern Africa. It forms part of the Maputaland-Pondoland-Albany biodiversity hotspot and encompasses four Ramsar wetlands of international importance (Lake St Lucia, the Mkhuze wetlands, Lake Sibaya and Kosi Bay). Large breeding populations of numerous species of birds and fish, as well as a host of other endangered species are protected within the Wetland Park. Apart from its ecological importance, resources from the Wetland Park are also used by nearby communities for domestic and agricultural needs. Organochlorine pesticides (OCPs) have been used extensively in the regions surrounding the Wetland Park for agricultural and malaria control purposes, yet few data exist on the local environmental and social impacts of these compounds. This study investigated the distribution and accumulation of OCPs in surface sediments (n = 45), fish tissue (n = 51), crocodile fat (n = 15), and coral tissue (n = 9) from the Wetland Park to assess potential ecological and human health risks. Substantial OCP concentrations were detected in all samples analysed. Total OCP concentrations in sediment ranged between 120 and 911 ng g-1 dw, with ΣHCH (26–283 ng g-1 dw) and ΣDDT (34–262 ng g-1 dw) the dominant contaminants. These concentrations are among some of the highest detected globally this century, with most far exceeding international soil quality guidelines. Total OCP concentrations in fish tissue samples from Oreochromis mossambicus (Mozambique tilapia) and Clarias gariepinus (African sharptooth catfish), ranged between 2953 and 8740 ng g-1 lw, with all residue concentrations significantly higher than sediment values. Levels in the majority of fish samples exceeded European Commission maximum residue limits and a preliminary risk assessment indicated potential dietary risks associated with exposure to heptachlor, heptachlor epoxide and dieldrin. Nile crocodiles are exposed to OCPs throughout their range within iSimangaliso Wetland Park and contain some of the highest residue concentrations ever recorded in crocodilian fat tissue. DDT and its metabolites were the dominant compounds detected in most samples, with ΣDDT concentrations ranging between 520 and 3100 ng g-1 ww. Elevated levels of other OCPs were also detected, including lindane (67 – 410 ng g-1 ww), aldrin (150 – 620 ng g-1 ww) and heptachlor (170 – 860 ng g-1 ww). The analysis of coral tissues revealed that OCPs also enter the marine environment, with ΣOCP concentrations detected in coral tissues varying between 2300 and 3000 ng g-1 ww. ΣDDT (140-460 ng g-1 ww), Σdrin (350-900 ng g-1 ww), Σchlor (390-1400 ng g-1 ww) were the dominant residues detected. This study represents the first detailed investigation into the distribution and accumulation of OCPs in iSimangaliso. The concentrations detected in the various environmental components analysed present a number of ecological and human health issues. A full evaluation of the ecological and human health effects associated with OCP contamination are beyond the scope of this thesis, although future assessments would aid in developing appropriate management practices in the region. The continued use of OCPs has potentially serious implications for wildlife conservation in the region and a need for greater understanding of the risks associated with OCP exposure is required. The findings from this study highlight the need for further and detailed investigations into the bioaccumulation and ecotoxicological implications of these OCPs in the aquatic food web, in both freshwater and marine environments. Specifically, further work examining the impact of OCPs on crocodiles and coral reef health is proposed. A more in-depth risk assessment is also recommended to better evaluate the impact of OCP exposure on residents in communities surrounding the Wetland Park.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, University of the Witwatersrand University of the Witwatersrand, Johannesburg, 2017
Keywords: Pesticides--Environmental aspects--South Africa; Pests--Control; Pesticides